Relationship between Belief in Determinism/Free Will and Mindfulness: Experiment I (Journal of Organizational Psychology, 2017)
This study examined possible interactions between mindfulness and induced beliefs in free will/ determinism. Participants read either free will, determinism or neutral induction statements. Participants were also identified as having either high or low in mindfulness based on their MAAS scores. Then, participants answered a number of questionnaires. Those with higher mindfulness scores reported experiencing more positive affect and less negative affect than low mindful participants. There were several 2 (mindfulness) X 3 (type of induction) interactions for participants’ reaction times to some questionnaires. Results are discussed in terms of improved attentional processing and in terms of high/low decision boundaries.
Keywords: Organizational Psychology; MAAS